2022
DOI: 10.1186/s12882-022-02727-5
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin in Acute Kidney Injury (EAKI): a pragmatic randomized clinical trial

Abstract: Background Treatment with erythropoietin is well established for anemia in chronic kidney disease patients but not well studied in acute kidney injury. Methods This is a multicenter, randomized, pragmatic controlled clinical trial. It included 134 hospitalized patients with anemia defined as hemoglobin < 11 g/dL and acute kidney injury defined as an increase of serum creatinine of ≥ 0.3 mg/dL within 48 h or 1.5 times baseline. One arm received r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
4
4
0
Order By: Relevance
“…A previous study, which we conducted in CKD dogs showed that anemia affected the 63% of the canine population, with a significant increase in its frequency with the progression of the IRIS stage [10]. The elevated frequency of anemia in our population of AKI dogs was in line with human medicine, in which anemia is considered a common disorder [15]. In human medicine, a causal relationship between AKI and anemia was identified, not only as AKI is timely antecedent to anemia, but also because higher grades of AKI, or longer duration of the disease are usually associated with more severe forms of anemia at three and six months.…”
Section: Discussionsupporting
confidence: 79%
“…A previous study, which we conducted in CKD dogs showed that anemia affected the 63% of the canine population, with a significant increase in its frequency with the progression of the IRIS stage [10]. The elevated frequency of anemia in our population of AKI dogs was in line with human medicine, in which anemia is considered a common disorder [15]. In human medicine, a causal relationship between AKI and anemia was identified, not only as AKI is timely antecedent to anemia, but also because higher grades of AKI, or longer duration of the disease are usually associated with more severe forms of anemia at three and six months.…”
Section: Discussionsupporting
confidence: 79%
“…A previous study, which we conducted in CKD dogs, showed that anemia affected 63% of the canine population, with a significant increase in its frequency with the progression of the IRIS stage [10]. The elevated frequency of anemia in our population of AKI dogs was in line with human medicine, in which anemia is considered a common disorder [15]. In human medicine, a causal relationship between AKI and anemia was identified, not only because AKI is a timely antecedent to anemia, but also because higher grades of AKI, or longer duration of the disease are usually associated with more severe forms of anemia at three and six months.…”
Section: Discussionsupporting
confidence: 79%
“…A retrospective study by Park J and Colleagues in AKI patients showed that treatment with EPO was unable to lower transfusion requirements, and to improve renal recovery or survival [22]. Similar findings were reported in a recent multicentric study by Aoun M. and colleagues, in which the group of AKI human patients treated with EPO did not show a better outcome or a lower need for blood transfusion compared to the control group [15]. A key role in the pathophysiological mechanism of anemia may be played by indoxyl sulfate.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations